Advancements and Challenges in Text-to-Image Synthesis: A Comprehensive Review - Khushboo Patel (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Text-to-image synthesis, a subfield of generative adversarial networks (GANs), is an exciting area of research that aims to bridge the gap between natural language understanding and computer vision. With recent advancements in deep learning techniques and the availability of large-scale datasets, significant progress has been made in generating realistic and diverse images from textual descriptions. Generating Hi-Fidelity, complex images from text are a challenging task. The ability to generate real images from textual descriptions has profound implications in various domains, including computer vision, multimedia, and virtual reality. This paper provides an in-depth study of state-of-the-art techniques and methodologies for text-to-image synthesis. Also, this paper discusses the various architectural enhancements, models, and evaluation metrics. Finally, the paper concludes by identifying open research issues and future directions that can enhance the performance and capabilities of text-to-image synthesis systems.